Analisis Kepuasan Masyarakat pada Pengelolaan Dana Desa - Ilham Perdana Putra; Titi Darmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to find out how the community's satisfaction with the management of village funds in Tik Teleu Village, Lebong Regency. The research method using descriptive quantitative research methods. In this study there are three ways of data collection techniques, namely observation, interviews and documentation. The results of the study can be seen, that first, community satisfaction in managing village funds in general is still not satisfied. The community considers that the village government is less transparent in the management of village and community funds as well as the performance of the village government is still not optimal and is considered slow. Second, the level of community participation in the management of village funds is also less involved. The conclusion shows that in the management of village funds, community leaders are only involved at the level of community participation consisting of providing suggestions/proposals during the initial deliberation on village fund planning. However, after the village funds were disbursed, community leaders did not know that some even thought that the planning was not in accordance with what had been discussed. Keywords: Satisfaction Level, Village Fund Management